Exposure to interparental intimate partner violence and the development of borderline features in adolescents. (May 2020) - Sharp, Carla; Vanwoerden, Salome; Jouriles, Ernest N.; Godfrey, Donald Andy; Babcock, Julia; McLaren, Veronica; McFarlane, Judith; Brashear, Barbie; Walton, Quenette; Temple, Jeff R.
Abstract: Background: Due to associated trauma, exposure to intimate partner violence (IPV) is considered a form of child maltreatment, and is associated with heightened risk for mental health problems. Objective: To evaluate associations between exposure to interparental IPV and the prospective development of borderline features in adolescents. Participants and setting: A diverse sample of 1, 042 adolescents were recruited from public high schools throughout southeastern United States and followed annually for 5 years. Baseline mean age was 15.09 (SD = .79; range 13–18), and 56 % of the sample was female; 31.4 % (n = 327) were Hispanic, 29.4 % (n = 306) were White/not Hispanic, 27.9 % (n = 291) were African American, 3.6 % (n = 38) were Asian or Pacific Islander, and 7.7 % (n = 80) were mixed or another race. Methods: Exposure to interparental IPV and the quality of the parent-child relationship were assessed at baseline. Borderline features were assessed annually for the each of the five follow-up timepoints. Latent growth curve modeling was used to estimate the course of change of BPD features over time. Results: Consistent with expectations, and controlling for quality of parent-child relationships and sociodemographic confounds, findings demonstrated that IPV exposure related to both cross-sectional association between interparental IPV and adolescents' borderline features and change in borderline features over a 5-year period. Conclusion: Adolescents who had witnessed interparental IPV were more likely to have higher levels of BPD features at baseline and to deviate from the typically observed normative decline in BPD features over the 4-year follow-up period.